IMPLEMENTATION OF PHET LEARNING MEDIA IN EFFORTS TO IMPROVE ACTIVITIES AND PHYSICS LEARNING OUTCOMES OF STUDENTS IN CLASS XI SMA 4 PEKANBARU - Nefrita Nefrita (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
The implementation of learning, especially Physics, is currently based on the results of observations still experiencing several obstacles. The tendency of passive students and learning outcomes as part of students still shows results that have not been maximal. Based on this fact, this classroom action research was carried out to improve the learning process and physics learning outcomes of students in the fluid material in class XI IPA1 SMA 4 Pekanbaru, using PHET (Physics Education Technology) media. The type of research conducted is classroom action research consisting of 2 cycles, with the subject are students of class XI SMA Negeri 4 Pekanbaru. Time for the implementation of odd semester 2018/2019 academic year. Data collection techniques used observation sheet instruments for learning activities and fluid material test sheets for physics learning outcomes. Data is analyzed descriptively in percentage representation. The results of the research showed that the learning activities of students had increased from cycle I to cycle II. Furthermore, for physics learning outcomes, students increase from the first cycle to cycle II, with the average results obtained by the good category. Therefore, the application of PHET-based information technology simulation media in physics learning can improve learning activeness and learning outcomes of class XI students of SMA 4 Pekanbaru.